ANALISA PERUBAHAN SUSEPTIBILITAS DAN KOMPOSISI SERTA UKURAN PARTIKEL OKSIDA BESI SEBAGAI FUNGSI KECEPATAN PUTARAN TABUNG BALL MILLING - Indah Nurhidayah; Salomo Sinuraya; Erwin Amiruddin; Rahmondia Nanda Setiadi (Universitas Riau, 2023)
The magnetic susceptibility, composition and particle size of natural sand has been carried out in Rokan River, Riau Province regency have been determined. Iron sand samples were processed using an iron sand separator (ISS). The magnetic and non-magnetic particles of ISS products were separated using neodymium iron boron (NdFeB) magnet. The product of ball milling (BM) with tube rotational speed functions of 100 rpm, 150 rpm, 200 rpm was milled for 80 hours with BM size of 2 cm. The magnetic susceptibility were determined based on magnetic induction of a selenoid measured using Probe Magnetic Pasco PS-2162. The composition of Rokan river natural sand was measured using x-ray fluorescence. The magnetic particles are determined using scanning electron microscope. The results showed that the magnetic susceptibility increases with increasing BM tube rotational speed 28,138.79 × 10-5 (100 rpm), 29,374.88 × 10-5 (150 rpm), and 30,955.32 × 10-5 (200 rpm). The composition of Fe in the sample has increased from 32.686% to 35,865%, while for Si has decreased from 38.604% to 33.729%. The particle size of natural sand for 80 hours milling displays the particle sizes from 883.4 for 100 rpm to 655.81 for the smallest particle size of the samples synthesized with 200 rpm.